IMPLEMENTASI KONSEP NATION BRANDINGANHOLT DALAM PENYELENGGARAAN ASIAN GAMES JAKARTA- PALEMBANG 2018 - Muhammad Yamin (Indonesian Journal of International Relations, 2020)
The 2018 Jakarta-Palembang Asian Games was held aiming to make this moment an Indonesian nation branding effort. Nation branding is considered as an important thing since it could increase nation’s visibility, reputation and product recognition in global market. This paper aims to analyse the implementation of Indonesia’s nation branding in Asian Games 2018. This research uses nation branding hexagon concept from Simon Anholt which consists of six aspects, these are people, tourism, exports, governance, investment and immigration, and culture and heritage. Research method used is descriptive qualitative with literature review as data collection technique. The research found out six aspects of nation brand hexagon has been implemented in various series of events in Asian Games 2018. It brings positive impact to Indonesia’s public image, especially the participating country in Asian Games 2019.